2022
DOI: 10.1002/adfm.202209980
|View full text |Cite
|
Sign up to set email alerts
|

Improved Solubility in Metavalently Bonded Solid Leads to Band Alignment, Ultralow Thermal Conductivity, and High Thermoelectric Performance in SnTe

Abstract: SnTe is an emerging Pb‐free thermoelectric compound that has drawn significant attention for clean energy conversion. Chemical doping is routinely used to tailor its charge carrier concentration and electronic band structures. However, the efficacy of dopants is often limited by their small solubility. For example, only 0.5% Ag can be incorporated into the SnTe matrix. Yet, significantly more Ag (>7%) can be dissolved if SnTe is alloyed with AgSbTe2. This large enhancement of solubility can be understood from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…52 Both SnTe and AgSbTe 2 employ metavalent bonding as identified by an unusual bond rupture in atom probe tomography. 52 The solid solubility limit of Ag in SnTe has been significantly enhanced due to the coexistence of two S6). The line scanning EDS results (Figure S7) clearly indicate that the V elements are rich around the nanoprecipitates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Both SnTe and AgSbTe 2 employ metavalent bonding as identified by an unusual bond rupture in atom probe tomography. 52 The solid solubility limit of Ag in SnTe has been significantly enhanced due to the coexistence of two S6). The line scanning EDS results (Figure S7) clearly indicate that the V elements are rich around the nanoprecipitates.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that the solubility limit can be significantly enhanced by alloying SnTe with compounds employing the same chemical bonding mechanism . Both SnTe and AgSbTe 2 employ metavalent bonding as identified by an unusual bond rupture in atom probe tomography . The solid solubility limit of Ag in SnTe has been significantly enhanced due to the coexistence of two metavalent bonding systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] However, the stoichiometric SnTe has a poor thermoelectric performance. Recently, the thermoelectric performance of SnTe has been improved due to a deeper theoretical understanding 11,12 and imaginative experimental methods. [13][14][15][16][17][18][19][20][21] Compared to thermoelectric performance (zT and efficiency), the economic viability of the fabrication process is equally important for the large-scale industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…8–10 However, the stoichiometric SnTe has a poor thermoelectric performance. Recently, the thermoelectric performance of SnTe has been improved due to a deeper theoretical understanding 11,12 and imaginative experimental methods. 13–21…”
Section: Introductionmentioning
confidence: 99%